2012
DOI: 10.1136/thoraxjnl-2012-201926
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety of inhaled medications in patients with chronic obstructive pulmonary disease: systematic review and mixed treatment comparison meta-analysis of randomised controlled trials

Abstract: BackgroundThe active-treatment comparative safety information for all inhaled medications in patients with chronic obstructive pulmonary disease (COPD) is limited. We aimed to compare the risk of overall and cardiovascular death for inhaled medications in patients with COPD. Methods Through systematic database searching, we identified randomised controlled trials of tiotropium Soft Mist Inhaler, tiotropium HandiHaler, long-acting β2 agonists (LABAs), inhaled corticosteroids (ICS), and LABA-ICS combination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 25 publications
3
121
0
3
Order By: Relevance
“…Despite this, the two meta-analyses, which reported data on the 5 mg preparation alone, both reported an increased risk of death of 1.46 (95% CI 1.01-2.10) [3] ( fig. 1) and 1.46 (95% CI 1.01-2.14) [5], respectively, and a 5 mg dose was also associated with an increased risk of cardiovascular death, OR 2.18 (95% CI 1.15-4.41) [5].…”
Section: Inclusion Of 10 Mg Datamentioning
confidence: 97%
See 4 more Smart Citations
“…Despite this, the two meta-analyses, which reported data on the 5 mg preparation alone, both reported an increased risk of death of 1.46 (95% CI 1.01-2.10) [3] ( fig. 1) and 1.46 (95% CI 1.01-2.14) [5], respectively, and a 5 mg dose was also associated with an increased risk of cardiovascular death, OR 2.18 (95% CI 1.15-4.41) [5].…”
Section: Inclusion Of 10 Mg Datamentioning
confidence: 97%
“…Previous research has shown that allocation of the cause of death in clinical trials of tiotropium is not straightforward and that ''all-cause'' mortality may be a stronger endpoint than cause-specific mortality because of diagnostic uncertainty [18]. Despite this, both the BMJ and Thorax systematic reviews found an increased risk of cardiovascular death with tiotropium Respimat compared with placebo, RR 2.05 (95% CI 1.06-3.99) [3], and OR 1.96 (95% CI 1.07-3.60) [5], respectively. This twofold increase in cardiovascular mortality accounts for about half the increase in all-cause mortality.…”
Section: All-cause Mortality and Cause-specific Mortalitymentioning
confidence: 99%
See 3 more Smart Citations